Development of a Personnel and Payroll Information System at Madrasah Ibtidaiyah Misbahun Nasyiin School - putra purnama; Dian Pratiwi; Agus Salim (Intelmatics, 2023)
MI. Misbahunnasyiin is an Islamic educational institution located on Jl Raden Saleh, Tangerang. MI Misbahunnasyiin has administrative and financial data that is still recorded manually, which is very dangerous and vulnerable or at risk of data loss and damage. so that this research aims to find a solution to solve this problem by making applications related to digitalized payroll and staffing so that it can facilitate user performance and solve problems that existed before. Then writing study This is expected to simplify and increase efficiency in data processing and help develop information systems at the MI Misbahunnasyiin school using the language of them program PHP and MySql as server database.